Photovoltaic and battery systems sizing optimization for ultra-fast charging station integration. (25th August 2022) - Leone, Carola; Peretti, Carlo; Paris, Andrea; Longo, Michela
Abstract: The installation of Ultra-Fast Charging stations (UFCS) is of vital importance to enhance and support the global shift to electric mobility. However, since UFCSs require a huge amount of energy in short period of time, their integration with the energy transmission and distribution grids will lead to a considerable number of technical challenges. To mitigate these negative aspects the incorporation of a Photovoltaic (PV) power plant and a Battery Energy Storage System (BESS) in the station systems seems crucial. In this paper an optimization study to find the size of these additional components is carried out. The final aim is to find their optimal dimensions to make the integration the most convenient as possible from an economic point of view. To achieve such a purpose, a single-objective optimization problem is simulated. The objective function aims to maximize the Net Present Value (NPV) of the overall charging station. The single-objective function is optimized through a genetic algorithm (GA) and the optimization toolbox embedded in the MATLAB software has been used to run the proposed optimization. The results highlight how the configuration complemented with the PV plant and the BESS is better from a technical-economic perspective. As a matter of fact, the profitability of such UFCS will be 7.5 % higher than the solution without additional components. Highlights: Simulation of EVs charging demand in an UFCS with probabilistic approach Optimal size of a UFCS integrated with PV and BESS by maximizing the NPV. Identifying the impacts of different EMS on the optimal results.